American Gods - Neil Gaiman (USA William Morrow, 2011)
The extraordinary, highly acclaimed epic novel from storytelling genius Neil Gaiman. After three years in prison, Shadow has done his time. But as the time until his release ticks away, he can feel a storm brewing. Two days before he gets out, his wife Laura dies in a mysterious car crash, in adulterous circumstances. Dazed, Shadow travels home, only to encounter the bizarre Mr Wednesday claiming to be a refugee from a distant war, a former god and the king of America. Together they embark on a very strange journey across the States, along the way solving the murders which have occurred every winter in one small American town. But the storm is about to break... Disturbing, gripping and profoundly strange, Gaiman's epic novel sees him on the road to the heart of America.
Keywords: Fantasy